Anthology of English literature - Greenblatt, Stephen (W.W. Norton, 2012)
Includes bibliographical references and indexes; Include 6 volumes: V.A. the middle ages. -- V. B. sixteenth century and the early seventeenth century. -- V. C. The restoration and the eighteenth century. -- V. D. the romantic period. -- V. E. the victorian age. -- V. F. the twentieth century and after; NV Văn học phương Tây